Perceived service quality of zakat institution among Muslim businessmen in Malaysia - Saad, Ram Al Jaffri; Abdul Wahab, Muhammad Syahir; Md Hussain, Md Hairi (IP Publishing LLC, 2018)
A mail survey was conducted to examine perceived service quality towards zakat institution among 227 Muslim businessmen in one of the states in Malaysia. The research data was analyzed using descriptive statistic. The findings indicated that the majority of respondents rated three aspects of the quality, namely, tangibles, reliability and courtesy as “Good”. Meanwhile, credibility, competence, responsiveness, access, understanding and communication were aspects that rated as “Bad”. Based on the findings, zakat institution needs to develop and implement appropriate strategies to improve its service quality in many aspects. The research implications and suggestions for future research were also discussed.